PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN KETRAMPILAN MEMBUATBATIK SEDERHANA BAGI SISWA TUNARUNGU - AGUSTINAH, FARIDAH (Jurnal Pendidikan Khusus, 2016)
ABSTRACT                    Based on observations in SLB Pandaan stated that, VIII grade deaf students do not know how to make a simple batik. The purpose of this research is to apply the method of demonstration to improve the skills of batik making it simple for deaf students of class VIII SLBN Pandaan Pasuruan. This research is a classroom action research using action research model of Kemmis and Taggart. Techniques of data collection is done by using observation and tests, while the data were analyzed using descriptive data analysis. This research was conducted in three cycles. This is because the first cycle, there are still many shortcomings then resumed in cycle 2 and cycle 3. Implementation of the demonstration method possible for deaf students in the eighth grade SLB Pandaan has a basic concept to learn how to make a simple batik. With the results of a study conducted by researchers showed an increase after the action was held in cycle 1, cycle 2 and cycle 3. The improvement can be seen from the students who can not make this into a simple batik can make this simple batik correctly. It can be concluded that the use motode demonstration can be applied to the material of batik making it simple for deaf students Keywords: Batik simpler, method demonstrations, Deaf